No "global Britain" after Brexit: Leaving the EU weakens UK foreign and security policy, closer ties remain in Germany's interest - Claudia Major; Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2018)
Under the leitmotif of 'Global Britain', the British government is painting Brexit as a unique opportunity to rethink its foreign and security policy: stronger, more influential, more global. The heart of the concept is a global outlook and bilateral agreements to compensate the loss of EU ties. In fact, however, the looming reality of Brexit appears to be weakening the United Kingdom diplomatically and spotlighting the constraints that individual nation states face. Confronted with rising transatlantic tensions and a resurgent China and Russia, the EU has no interest in having a weakened and insecure neighbour right across the Channel. But neither will the EU offer the UK special access to its foreign and security policy as a third country. In parallel to the Brexit negotiations, Germany should therefore keep channels open by intensifying the bilateral relationship and proposing new European foreign policy consultation formats.
Keywords: 320